Interview James Kinyangi, East Africa Regional Program Leader - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
James Kinyangi, CCAFS East Africa Regional Program Leader, is being interviewed about the benefits of targeting vulnerable communities in research programs and what CCAFS is doing in East Africa to make sure women and youth benefit from activities. James was also asked what smallholder farmers' want from the COP18 climate conference taking place in Doha, Qatar in November-December 2012.